Student interaction and text revision in a trained peer-response ESL writing classroom / Kamalanathan M. Ramakrishnan - Kamalanathan M. , Ramakrishnan (2018)
Peer-response is an important aspect of the process approach to teaching writing which has gained increasing attention in the ESL context. It offers great opportunities for ESL student-writers to share their writing evaluate the work of their peers and discuss their observations and opinions about writing in an authentic learning environment. There are, however, gaps in current research about the student-writers’ discourse in the peer-response groups, how that discourse affects their revisions and writing development. The interactive and collaborative learning theories that underlie the process writing approach to learning to write in a second language made it possible to observe the participants in the peer-response activity over a period of fourteen weeks. The sixteen ESL student-writers from a public university in Malaysia, purposefully selected, were from homogenous linguistic, cultural and socio-economic backgrounds. Extensive training, which focussed on affective, cognitive, socio-cultural and linguistic aspects, was provided to the participants before they participated in the peer-response activity. The peer-response groups for this study were structured to incorporate collaborative learning. The participants worked in pairs to write the first draft of an essay of their choice and two writing-pairs in a group took turns to respond to each other’s draft. The peer-response sessions were recorded and transcribed. After the peer-response sessions, the participants had the opportunity to make changes to their drafts. Participants turned in their first drafts and revised papers for analysis. Post-revision interviews were conducted to further understand the revision process. Data for this qualitative case study consisted of the participants’ first drafts and revised papers, peer-response checklists, transcripts of the peer-response and post-revision interview sessions as well as the researcher’s observation entries and field-notes. A thematic analysis method was used to analyze the data. The spoken and written data of the eight writing-pairs offered a variety of indications regarding the types of interactions that occurred during the peer-response sessions, the types of feedback that produced the most positive changes and improvement to the revised papers. The participants were able to provide valid suggestions for each other’s drafts, respond critically to peer feedback and incorporate high proportions of valid peer suggestions in their revisions. This improved the quality of the revised papers, facilitated autonomous writing skills and development of independent writers. The revision process improved the student-writers’ critical skills and subsequently enabled them to improve their own drafts. Training the participants for the peer-response activity improved the quality and quantity of peer interaction about the drafts and revision strategies. This study has offered some new insights into the forms, functions and effectiveness of trained peer-response in a tertiary-level ESL writing classroom. The spoken data offered some indications that this activity can be pedagogically useful in the ESL setting because it promotes interaction and negotiation of meaning among the student-writers. It also creates an authentic atmosphere in which ESL student-writers can share their written drafts with their peers and comment on their drafts.